STUDY ON THE PARAMETER OPTIMIZATION OF VALVE HEAD OF VERTICAL WELL INCLINOMETER (MT) - TANG LiPing; LIU ChenXi; ZHANG Lei; LI FuQiang; XIA HongYun; YANG Jie; DING Jun (Jixie qiangdu)
The vertical well inclinometer is widely used in downhole data measurement, wherein the mud pulse generator used for data transmission has substantial significance to the accuracy and stability of data. For this instrument, the performance of its mud pulse generator valve head is the key to ensure the efficient, accurate and complete transmission of downhole data. Firstly, the structure of pulse generator in the vertical well inclinometer is described, followed by the presentation of the physical and theoretical model of pulse generator valve head. Based on the erosion theories and thin-wall hole throttling model, the main parameters that affect the performance of pulse generator valve head are determined, including the throttling hole slot angle α and the valve head angle β. Secondly, with using the discrete phase model（DPM）, the influences of throttle slot angle α and valve head angle β on the flow field characteristics near the valve head and the pressure distribution of the valve head are investigated. In terms of the simulation, an optimized parameter set of the valve head is α=25°and β=45°. Finally, valve heads with optimized parameters are tested in a certain well of Dixi, showing a good accuracy with the numerical simulation with comparing the results before optimization.